2010
DOI: 10.1002/stem.300
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Determines Mesodermic Differentiation of Mouse Embryonic Stem Cells by Activating Class IIa Histone Deacetylases: Potential Therapeutic Implications in a Mouse Model of Hindlimb Ischemia

Abstract: In human endothelial cells, nitric oxide (NO) results in class IIa histone deacetylases (HDACs) activation and marked histone deacetylation. It is unknown whether similar epigenetic events occur in embryonic stem cells (ESC) exposed to NO and how this treatment could influence ESC therapeutic potential during tissue regeneration. This study reports that the NO-dependent class IIa HDACs subcellular localization and activity decreases the global acetylation level of H3 histones in ESC and that this phenomenon is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 47 publications
3
46
1
Order By: Relevance
“…While NO has been reported to control T-Bra levels in ESCs recently (Spallotta et al, 2010), we show here for the first time that NO potentially crosstalks with Wnt/CatnB signaling during primitive streak formation in ESCs to regulate T-Bra. Previous studies have speculated that this NO/Wnt crosstalk plays a role in colon cancer, leukemia, and colitis (Williams et al, 2003;Nath et al, 2005;Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 45%
“…While NO has been reported to control T-Bra levels in ESCs recently (Spallotta et al, 2010), we show here for the first time that NO potentially crosstalks with Wnt/CatnB signaling during primitive streak formation in ESCs to regulate T-Bra. Previous studies have speculated that this NO/Wnt crosstalk plays a role in colon cancer, leukemia, and colitis (Williams et al, 2003;Nath et al, 2005;Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 45%
“…6 HDAC7 is a member of the class II HDACs and has been linked to cardiovascular diseases. [7][8][9][10][11][12][13] Several pioneering studies have demonstrated that HDAC7 plays a crucial role in early embryonic development, 7 angiogenesis, 8,9 and SMC differentiation. 11 Moreover, HDAC7 can suppress endothelial cell proliferation 12 and responds to growth factors such as vascular endothelial growth factor and PDGF.…”
mentioning
confidence: 99%
“…Although NO production and endothelial nitric oxide synthase have been shown to be greater in longer living rodents, NO donors do not seem to influence animal maximum lifespan (Csiszar, et al, 2007). However, it has been shown both that NO can regulate telomerase activity (Farsetti, et al, 2009) and that it has a profound impact on mouse embryonic stem cell differentiation towards a cardiovascular fate (Spallotta, et al, 2010). Data on the effects of NO on hCSC are still missing.…”
Section: Drug-based Strategy To Enrich In Non-senescent Cellsmentioning
confidence: 99%